Enhanced performance of Li-O2 battery based on CFx/C composites as cathode materials. (20th December 2015) - Wu, Chaolumen; Wang, Haibin; Liao, Chenbo; Yang, Jun; Li, Lei
Abstract: A hybrid air-electrode composed of a mixture of fluorinated carbon (CFx ) and Ketjen black (KB) active carbon composite materials was prepared to improve performance of Li-O2 battery. In the hybrid air-electrodes, four kinds of CFx materials including fluorinated graphite, fluorinated carbon fiber, fluorinated coke and fluorinated black carbon were utilized as lithium insertion materials. The physical properties and morphologies of the KB and CFx carbon materials were characterized by Brunauer-Emmett-Teller (BET), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Scanning electron microscopy (SEM) measurements. Compared with the conventional KB air-electrode, all the CFx /KB hybrid air-electrodes in Li-O2 batteries showed higher specific discharge capacity, especially at high current density. Among these CFx /KB hybrid air-electrodes, the fluorinated graphite based electrode showed the best electrochemical performance in Li-O2 battery due to its highest discharge capacity of the fluorinated graphite material in the Li/CFx primary battery, highest specific surface area, and highest total pore volume. The electrochemical performance of Li-O2 and Li-air batteries using the hybrid air-electrodes with the different fluorinated graphite: KB weight ratio, including specific charge and discharge capacity, cycling stability and rate capability were systematically investigated. At a current density of 0.5 mA cm −2, the fluorinated graphite based air-electrode delivered a high specific discharge capacity of 1138 mAh g −1 in Li-O2 batteries, which was more than four times than that of the conventional KB air-electrode (265 mAh g −1 ) under same testing conditions. The battery assembled with the fluorinated graphite based air-electrode exhibited better cycling stability than that of the battery assembled with the conventional KB air-electrode.